2008
DOI: 10.1001/archpedi.162.6.513
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D Among Healthy Children in the United States

Abstract: Although overt vitamin D deficiency is no longer common in US children, lesser degrees of vitamin D insufficiency are widespread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
113
1
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 49 publications
15
113
1
6
Order By: Relevance
“…Hypovitaminosis D was very common among Saudi children and adolescents in this study, similarly to findings obtained in the US [15] and Qatar [16]. Interestingly, moderate to severe hypovitaminosis D was already documented as very common among young, normal adult Saudis in 1981 [17].…”
Section: Discussionsupporting
confidence: 89%
“…Hypovitaminosis D was very common among Saudi children and adolescents in this study, similarly to findings obtained in the US [15] and Qatar [16]. Interestingly, moderate to severe hypovitaminosis D was already documented as very common among young, normal adult Saudis in 1981 [17].…”
Section: Discussionsupporting
confidence: 89%
“…In a study on Costa Rican asthmatic children, 28% showed insufficient levels of vitamin D (,30 ng?mL -1 ), and an inverse relationship was observed between 25-hydroxyvitamin D levels and total immunoglobulin E, eosinophil count, use of anti-inflammatory medication in the previous year, increased airway responsiveness to methacholine and any hospitalisation in the previous year. In our study, only 11% of the patients and 12% of healthy controls had desirable 25-hydroxyvitamin D levels (o30 ng?mL -1 ), and this finding was not completely unexpected, as the study was conducted during the winter/ early-spring time and our town is located at a latitude of 45u279 N. People living above the 35th latitude cannot produce adequate pre-vitamin D3 during the winter [18], and in our country (Italy) foods are not fortified with vitamin D [19]. The fact that almost all our children had insufficient or deficient levels of 25-hydroxyvitamin D is worrying; although those levels have been set for optimal calcium, phosphorus and bone metabolism, there are proposals that concentrations .40 ng?mL -1 (100 nmol?L -1 ) may be essential for optimal immune functioning and overall health [20], but no child in our study population reached such levels.…”
Section: Discussionsupporting
confidence: 46%
“…African Americans are more prone to be deficient because of higher skin melanin levels. 70 Vitamin D inadequacy constitutes a largely unrecognized epidemic in many populations worldwide [71][72][73] It has been reported in healthy children, 74 adolescents 75 and adults. 76,77 Vitamin D and prostate health Normal and malignant prostate cells contain VDRs, [78][79][80] which mediate the antiproliferative action of 1,25(OH)2D.…”
Section: Hypovitaminosis Dmentioning
confidence: 99%